Rapid Needs Assessment in Digkilaan Philippines - Nasrodin, Jamaliah (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2022)
Digkilaan is one of the hinterland barangays in a highly urbanized city of Iligan, a lone district under Lanao del Norte located in the Northern part of Mindanao. It has an area of 1,246.85 hectares. Agriculture-based production of rice, corn, banana, root crops and copra are the main sources of income of the barangay. In order to advance and foster community development, Barangay Digkilaan plans to make the most of the town's rich environmental resources and local heritage. However, there is limited information accessible about the community's natural, physical, and social resources. Hence, this study used Rapid Rural Assessment by employing its tools/techniques; community mapping, livelihood matrix ranking, & seasonal analysis. A set of Focus Group Discussions (FGD) and Key Informant Interviews were also conducted. The findings of FGD revealed that sewing generates the highest revenue for women. This is a result of the high demand for togas during graduation, the high demand for uniforms during the start of school, and other factors likecurtains. Additionally, renting out these products can bring in extra money. The third quarter of the year has the biggest demand for women's labor in terms of the women labor pattern, mostly because it coincides with the start of the school year when there is a high demand for school uniforms and a corresponding high demand for seamstresses. But when it comes to men's income, pag niyog or pag lubi come in first. The participants claimed that Barangay Digkilaan has a large number of coconut trees. In order to provide for their family's living expenses, they gather coconut from a coconut palm once a month, earning an estimated average revenue of thirty four thousand (Php34,000.00) per quarter. Furthermore, there are available markets in Iligan City for their harvested coconuts like GRANEX, GCT Coconut Trading, Immaculate Cocoline Industries, and more. These results were confirmed through KII. Detailed data of these resources play an important role in identifying and developing Digkilaan community’s local talents, skills, andproducts, and use this to help the local economy to generate employment opportunities and protect the environment. Hence, the rural rapid appraisal was carried out to know the resources available within its frontierland to assist the local government unit in identifying and developing local products that willmaximize their resources to promote and enhance their community.